Homo‐molecular Fluorescence Complementation for Direct Visualization of Receptor Oligomerization in Living Cells. (14th January 2019) - Song, Daesun; Jung, Yongwon
Abstract: Cell surface receptor oligomerization is an attractive target process for drug screening. However, simple but reliable (and thus high‐throughput) visualization methods for receptor oligomerization are still lacking. Herein, we report on a new single‐construct homo‐molecular fluorescence complementation (Homo‐FC) probe, which shows strong fluorescence signals by oligomerization of fused receptors in living cells with unexpectedly low background signals. Importantly, this high signal‐to‐noise ratio was not affected by expression level variations of fused receptors. The Homo‐FC probe was developed by optimized flopped fusion of split fragments of superfolder green fluorescence protein and subsequent surface charge engineering. Homo‐FC reliably visualized the oligomerization of diverse natural receptors such as GPCR, EGFR, and even cytosolic DAI.